Penerapan Model Pembelajaran Kooperatif Tipe Group Investigation dalam Meningkatkan Hasil Belajar Bahasa Indonesia pada Peserta Didik Kelas I SD 3 Peganjaran - Suharto, Fierdayanti Thania; Ratnasari, Yuni; Suhartati, Oktri; Suwarni, Suwarni (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to improve the Indonesian learning outcomes of 1st grade students of SD 3 Peganjaran through the application of a Group Investigation type cooperative learning model. Group Investigation is recommended as an innovative alternative to improve the quality of Indonesian learning in elementary schools because it involves active students and fosters independent thinking, communication skills, and cooperative skills. This study uses a Classroom Action Research (PTK) design with the Kurt Lewin model which includes planning, action, observation, and reflection. This research was carried out in two cycles in the even semester of the 2024/2025 academic year. The method of data collection through summative tests that are quantitatively descriptive analyzed to measure student learning completeness. The resulting data was analyzed in a quantitative descriptive manner. The results of the study showed a significant increase in each cycle. The pre-cycle showed learning completeness of 44%, increased to 75% in cycle I, and reached 100% in cycle II. This improvement shows that the group investigation model is effective in improving student learning outcomes